Design and development of an Indian classical vocal training tool - Sharma, Shraddha (Nanyang Technological University, 2020)
When learning any form of classical music vocals without a teacher, even subtle deviations can lead to wrong training, which can be diﬃcult to remedy in the future. In this research work, a real-time tool has been developed to deal with this situation by assisting people in learning Indian classical music. This tool will have a set of pre-deﬁned Swaras, Alankaras, and Ragas (Indian classical music concepts). Users can practice any musical piece from this set and the tool will inform them of the mistakes they make, by smartly matching their voice with the dynamically deﬁned pattern. Users are free to sing in any given scale, which they deﬁne in the beginning by singing the root note of their preferred scale.